ChemInform Abstract: Investigation of the Reaction of Dithiocarbamic Acid Salts with Trimethyl Orthoformate and Styrene Epoxide. Issue 14 (March 2016) - Ziyaei Halimehjani, Azim; Hajilou Shayegan, Mojtaba; Poshteh, Shiva Shakori; Amani, Vahid; Notash, Behrouz; Hashemi, Mohammad M.
Abstract: The title reactions proceed in the presence of BF3 ·OEt2 to give 1, 3‐dithietane or 1, 3‐dithiolane derivatives in good yields.